Internet connectivity disruption in Moldova (Moldova) - Voidly (2026)
CRITICAL severity disruption detected in Moldova. Confidence: 67%. Data sourced from IODA.
Network Disruption Incident ID: MD-2026-0017
Keywords: internet disruption; MD; disruption; critical